2019
DOI: 10.2478/picbe-2019-0010
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship Business Research Skills

Abstract: In recent years area of entrepreneurship has gained significant attention nationally and internationally. It is one of the main skills priorities of national governments and EU council. Traditionally associated with commercial activity, entrepreneurship has gained traction as a key competence necessary to allow society as a whole to adapt to the changing economic climate. Small and medium sized companies (SMEs) greatly contribute to employment and wealth in Europe but there are limited studies into the specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The students also confirmed that they developed their research skills in terms of collecting primary as well as secondary sources of data effectively. The students’ research skills play a significant role in achieving entrepreneurial success (Hamburg et al , 2019). Relatively, having competitive research skills will also help identify various opportunities surrounding the business.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The students also confirmed that they developed their research skills in terms of collecting primary as well as secondary sources of data effectively. The students’ research skills play a significant role in achieving entrepreneurial success (Hamburg et al , 2019). Relatively, having competitive research skills will also help identify various opportunities surrounding the business.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…An entrepreneur should possess good research skills to identify the customer needs, keep pace with the changes in the industry and compete in the field. Therefore, entrepreneurship courses should aim at developing students’ research skills because they play an important role in achieving entrepreneurial success (Hamburg et al , 2019). The students should be encouraged to read research articles and engaged in primary and secondary data collection and data analysis tasks (Naqvi, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Communication, digital skills, and teamwork allow learners to collaborate and exploit technology in the changing workplace. (Hamburg et al (2019).…”
Section: Knowledgementioning
confidence: 99%